Productive Zakat And Its Implications For Improving Mustahik Welfare - MHD. Nanang Hidayat; M.Ilham; Muhammad Fakhri Khairi; Khoiruddin (LP2M IAIN Palopo, 2026)
This study aims to analyze the concept, implementation forms, implications, and factors influencing the effectiveness of productive zakat in improving the welfare of those entitled to receive it. Productive zakat is viewed as a Sharia-based economic empowerment instrument that focuses not only on consumer assistance but also on creating sustainable income sources through business capital, training, and mentoring. This study used a literature review approach, examining various scientific journals discussing the implementation of productive zakat in zakat management institutions such as BAZNAS and LAZ in Indonesia. The analysis was conducted using content analysis and thematic synthesis techniques to identify implementation patterns, impacts, and supporting factors for the program's success. The study results indicate that productive zakat has significant implications for increasing mustahik's income, the sustainability of micro-enterprises, family economic stability, and improving quality of life. Furthermore, productive zakat also has broader socio-economic impacts, such as local business growth and employment. Program effectiveness is influenced by the professionalism of zakat institution management, the accuracy of mustahik selection, the quality of business mentoring and training, ongoing monitoring, and the motivation and readiness of mustahik to develop their businesses. With integrated management, productive zakat has great potential as a poverty alleviation strategy based on sustainable and socially just sharia economics.